The importance of melatonin in ovarian syndrome polycystic: A bibliographic review (Research, Society and Development, 2022)
Introduction: Polycystic Ovary Syndrome (PCOS) is characterized by a multiple and complex endocrine disorder that leads to hyperandrogenism, menstrual irregularity and can lead to infertility. In this review, we will present an overview of PCOS, by summarizing the clinical and epidemiological literature related to the disorders of this syndrome, and associating it with melatonin. Methodology: This is a descriptive qualitative study, called an integrative literature review, it is a relevant instrument in the communication of research results, facilitating the use of these results in clinical practice, as it provides a synthesis of the knowledge already produced and provides contributions to the improvement of health care, through research in scientific articles present in databases. traditional medical knowledge data: PUBMED/MedLine, Scopus, Embase, Cochranne. Results: Polycystic ovary syndrome affects thousands of women worldwide, being a very complex disorder of multiple endocrine order, linked to hyperandrogenism and menstrual disorder, which can cause a series of complications that lead to infertility. women who want to reproduce. Discovering ways of reversing and recovering the characteristics of female reproduction would reduce the anguish of millions of women in the world. Conclusion: Despite the positive influence of melatonin on reproductive function, we did not observe in the literature randomized controlled studies comparing its use in women with PCOS More studies should be undertaken in this regard. There is no consistent evidence for the systematic use of melatonin in women with PCOS or chronic anovulatory women.